2016
DOI: 10.1186/s13071-016-1906-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the burden of intestinal parasites affecting newly arrived immigrants in Qatar

Abstract: BackgroundIn the last decades, the enormous influx of immigrants to industrialized countries has led to outbreaks of parasitic diseases, with enteric infections being amongst the most frequently encountered. In its strategy to control such infection, Qatar has established the Pre-Employment Certificate (PEC) program which requires medical inspection before arrival in Qatar and which is mandatory for immigrant workers travelling to the country. To assess the reliability of the PEC, we conducted a survey of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…Because of the number of factors involved, this second phase was conducted in three separate stages. First model 1 was fitted with the significant familial factors from phase 1, and then a second model (model 2) was fitted with the environmental factors, and in each case also including age class and region of origin of subjects as these had been shown earlier to have had a significant effect on INFECTION (14). In a third stage the significant factors from models 1 and 2 were included in model 3 that also incorporated age class and region of origin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the number of factors involved, this second phase was conducted in three separate stages. First model 1 was fitted with the significant familial factors from phase 1, and then a second model (model 2) was fitted with the environmental factors, and in each case also including age class and region of origin of subjects as these had been shown earlier to have had a significant effect on INFECTION (14). In a third stage the significant factors from models 1 and 2 were included in model 3 that also incorporated age class and region of origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, fitting univariate models does not allow the influence of confounding factors and their interactions to be identified, so in the second phase of our analysis we fitted all the significant effects from phase 1 into multifactorial models and combined these with age class and region of origin, which had been shown in our earlier paper to have had an influence on parasitic infections in these same individuals (14).This showed that many of the factors identified by univariate analysis are likely to have arisen through confounding interactions between fitted factors. The minimum sufficient models thus generated showed that the prevalence of combined helminth infections was influenced only by An earlier study conducted in Sharjah investigated intestinal protozoan infection rates among both expatriates and locals, and the infection rate was reported as 7.7% (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Qatar, the most widely used methods for surveillance of enteric infections among newly arrived and resident workers still rely on coproscopy [ 15 ]. In this paper we assess a method based on PCR as an alternative to examination of stool samples by microscopy.…”
Section: Introductionmentioning
confidence: 99%